Abnormalities of Bell's phenomenon in amyotrophic lateral sclerosis: a clinical and electrophysiological evaluation. Issue 8 (August 1978) - Esteban, A; De Andrés, C; Giménez-Roldán, S
Abstract : A clinical and electromyographic study of oculomotor function was carried out in a series of 24 patients with amyotrophic lateral sclerosis (ALS). In 15 cases an alteration of Bell's phenomenon was found. In addition, three patients showed some impairment of conjugate ocular motility in the form of upward gaze paly. All cases had preserved oculocephalic reflexes in the vertical and horizontal planes. On clinical and electromyographic grounds, three degrees of altered Bell's phenomenon are suggested: attenuated (short and unsustained upward displacement of the eyeballs after forced closure of the eyelids), abolished (no upward displacement), and inverted (downward instead of upward displacement of the eyes). These oculomotor alterations were not directly related to the type of ALS at onset of the illness, nor with its duration. However they were correlated with the relative degree of the clinical bilateral pyramidal tract signs at the supraspinal level. The common involvement of the corticogeniculate tract in ALS could explain the unexpectedly high incidence of alteration of Bell's phenomenon found in this disease, but is is non-specific and similar lesions from different causes may also produce it.